Idiotype-specific intravenous immunoglobulin for therapy of immunoglobulin kappa free light chain deficiency - Adina Elena Stanciu; Monica Popescu; Dan Cristian Gheorghe (Taylor & Francis Group, 2019)
Deficient antibody production in patients with common variable immunodeficiency (CVID) is accompanied by an inability to produce free light chains (FLCs), particularly kappa (κ) FLC, due to B-cell dysfunction. We found that intravenous immunoglobulin (IVIg) administration, in a patient with CVID and (κ) FLC deficiency, for o short period of only 6 months, induced after discontinuation of treatment some kind of "long-lasting active immunity", leading to the secretion of immunoglobulin (κ) FLCs. A remarkable finding of our study is how effectively IVIg therapy led to a calculable (κ/λ) FLCs ratio, within the reference range. IVIg therapy may have functioned as an idiotype vaccine which induced a humoral response. To date, several questions remain open. For instance, from a clinical standpoint, we do not know whether this form of active immunotherapy has the potential to cure or just to control the immunoglobulin (κ) FLC deficiency. Further studies are necessary to confirm these findings.